Inulin rich carbohydrates extraction from Jerusalem artichoke (Helianthus tuberosus L.) tubers and application of different drying methods. (January 2018) - Rubel, Irene A.; Iraporda, Carolina; Novosad, Rocio; Cabrera, Fernanda A.; Genovese, Diego B.; Manrique, Guillermo D.
Abstract: In this study the operational extraction variables to obtain higher yields of inulin from Jerusalem artichoke tubers (JAT), as well as the optimal conditions to obtain a stable and dispersible powdered product by either spray or freeze drying, were studied. With this purpose, the powder yield, moisture content, water activity and flowability or products obtained by different experimental conditions were analyzed. Inulin rich carbohydrates (IRC) extraction was performed from lyophilized and ground tubers employing distilled hot water as solvent. It was proved that the solid:solvent ratio (S:S) was the critical variable in the extraction process, followed by temperature. Thus, the IRC extraction was optimal without ultrasound assistance, at 76 °C, employing a S:S of 1:16, during 90 min. In addition, the powder obtained by freeze-drying of the IRC extract showed advantages respect to powders obtained by spray-drying regarding the yield and considering that maltodextrin was not necessary as encapsulation agent. In another hand, spray drying process provided IRC powered materials with appropriate flow properties, and taking into account cost and time of production, this method should be considered as an alternative of freeze-drying. Graphical abstract: Highlights: Inulin from Jerusalem artichoke tubers was extracted in a water batch system. Inulin extraction conditions were optimized. Inulin powders were obtained by freeze and spray-drying. Physical properties of inulin powders were analyzed. Stable freeze-dried inulin powders were obtained.